2017
DOI: 10.1016/j.jtho.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Combined Immunotherapy and Antiangiogenesis for the Synergistic Treatment of Advanced NSCLC

Abstract: Over the past few years, there have been considerable advances in the treatments available to patients with metastatic or locally advanced NSCLC, particularly those who have progressed during first-line treatment. Some of the treatment options available to patients are discussed here, with a focus on checkpoint inhibitor immunotherapies (nivolumab and pembrolizumab) and antiangiogenic agents (bevacizumab, ramucirumab, and nintedanib). It is hypothesized that combining immunotherapy with antiangiogenic treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
162
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 203 publications
(166 citation statements)
references
References 59 publications
3
162
0
1
Order By: Relevance
“…VEGF plays a crucial role in mediating the immunosuppressive microenvironment. In particular, VEGFR2 inhibition is reported to significantly increase cluster of differentiation (CD)4‐positive and CD8‐positive T cell infiltration and reduce the number of Tregs and MDSCs within tumor tissues in mice . A recent experimental study showed that simultaneous inhibition of PD‐1 and VEGFR2 significantly suppressed tumor growth compared to monotherapy .…”
Section: Discussionmentioning
confidence: 99%
“…VEGF plays a crucial role in mediating the immunosuppressive microenvironment. In particular, VEGFR2 inhibition is reported to significantly increase cluster of differentiation (CD)4‐positive and CD8‐positive T cell infiltration and reduce the number of Tregs and MDSCs within tumor tissues in mice . A recent experimental study showed that simultaneous inhibition of PD‐1 and VEGFR2 significantly suppressed tumor growth compared to monotherapy .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the combination of bevacizumab and checkpoint inhibitors or other immunotherapies also seems to have a synergistic effect and is currently investigated for other solid tumor such as ovarian cancer. 19 When interpreting the findings of our report, some limitations typical for retrospective studies need to be kept in mind. Previously reported studies have used RECIST 1.1 criteria.…”
Section: Discussionmentioning
confidence: 95%
“…Emerging evidence that pro-angiogenic factors have immunosuppressive activity has suggested that agents targeting angiogenesis may be potentially synergistic with immunotherapy (6769). Data from literature indicate that VEGF influences lymphocyte trafficking, stimulates T regulatory cells and myeloid-derived suppressor cells, and inhibits T-cell development, thus favoring tumor immune escape (7072).…”
Section: Comments and Future Perspectivesmentioning
confidence: 99%